Glycolipid and Hormonal Profiles in Young Men with Early-Onset Androgenetic Alopecia: A meta-analysis - Rossella Cannarella (Nature Portfolio, 2017)
Abstract Hormonal and metabolic abnormalities have been reported in men with early-onset androgenetic alopecia (AGA). Although this has been ascribed to the existence of a male polycystic ovary syndrome (PCOS)-equivalent, data on this topic are inconsistent and this syndrome has not been already acknowledged. To evaluate if, already before the age of 35 years, any difference occurs in the glycolipid and hormonal profiles and in the body weight in men with AGA compared to age-matched controls, we performed a comprehensive meta-analysis of all the available observational case-control studies of literature, using MEDLINE, Google Schoolar and Scopus databases. Among 10596 papers retrieved, seven studies were finally included, enrolling a total of 1009 participants. Our findings demonstrate that young men with AGA have a slightly but significantly worse glycolipid profile compared to controls and a hormonal pattern resembling those of women with PCOS, already before the age of 35 years. Therefore, early-onset AGA might represent a phenotypic sign of the male PCOS-equivalent. The acknowledgement of this syndrome would be of importance to prevent the long-term consequences on health in the affected men. The glycolipid profile and the body weight should be monitored in men with AGA starting from the second decade of life.